A feasibility study in establishing "Cool Haus Ice Cream Parlor" at 3-B Zone IV, Dasmariñas, Cavite - Macleod, Alexander I., author; Broas, Joseph Albert L., author; De Ocampo, Ma. Cristina A., author; Mercado, Ma. Corazon Y., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2008)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2008.
Includes bibliographical references and appendices.
In English text.
Keywords: Ice cream, ices, etc; Desserts; Sundaes; Sorbet; Frozen treats; Feasibility study